Characteristics of Patients With Graves Disease and Intrathyroid Hypovascularity Compared to Painless Thyroiditis. (1st October 2014) - Uchida, Toyoyoshi; Shigihara, Nayumi; Takeno, Kageumi; Komiya, Koji; Goto, Hiromasa; Abe, Hiroko; Sato, Junko; Honda, Akira; Fujitani, Yoshio; Watada, Hirotaka
Abstract : Objectives: The purpose of this study was to assess the frequency and sonographic and laboratory characteristics of Graves disease with intrathyroid hypovascularity in Japanese patients and to compare these characteristics in patients with painless thyroiditis. Methods: A total of 194 consecutive patients with Graves disease and 21 patients with painless thyroiditis were enrolled. The patients underwent thyroid volume measurement, mean superior thyroid artery peak systolic velocity (PSV) measurement, power Doppler sonography, and proper blood testing to discriminate between Graves disease and painless thyroiditis. Based on the power Doppler sonographic findings, they were divided into 4 groups: from pattern 0 (most hypovascular thyroid) to pattern III (most hypervascular thyroid). Comparisons of multiple thyroid parameters were made among the groups. Results: The prevalence of Graves disease with pattern 0 (n = 27) was 13.9% among the patients with Graves disease. The sonographic and laboratory data for patients with Graves disease and pattern 0 were compared to those of the 21 patients with painless thyroiditis, which typically shows intrathyroid hypovascularity. Free triiodothyronine and thyroxine levels and the superior thyroid artery PSV were significantly lower in patients with Graves disease and pattern 0 than those with patterns I, II, and III ( P < .05). The thyroid volume and thyrotropin receptor antibody level were significantly lower in patients with Graves disease and pattern 0 than those with pattern III. In the comparison between patients with Graves disease and pattern 0 and those with painless thyroiditis and pattern 0, apart from thyrotropin receptor antibody, only the superior thyroid artery PSV was different. Conclusions: Although the clinical features of patients with Graves disease and intrathyroid hypovascularity were similar to those patients with painless thyroiditis, the superior thyroid artery PSV showed a moderate ability to discriminate these patients.